Interrogative Modality in Spoken Language : An Exploration of the Use of Modality in Educational Discourse - Jatiswa, Bayu Anggara Riyan; Rosadi, Pendi; Muhaimi, Lalu; Hadi, Makmur (Ethical Lingua: Journal of Language Teaching and Literature, 2025)
This study explores interrogative modality in educational discourse at SMA 7 Mataram, specifically in English language classrooms. The research aims to investigate how teachers utilize interrogative modality and to determine its impact on the learning process. Adopting a qualitative approach with a case study design, data were collected through classroom observations, audio recordings, and semi-structured interviews with four experienced English teachers. The analysis revealed that teachers employ diverse interrogative modalities, with "can" being the most frequently used (25%), followed by "could" (15%) and "would" (10%). These modalities serve different pedagogical functions, from facilitating simple recall to encouraging critical analysis. The strategic use of interrogative modality significantly enhanced the learning process in multiple ways. Student engagement increased from 50% to 80% throughout the semester in classes featuring analytical and evaluative questions. Students also demonstrated development in critical thinking skills, with responses evolving from brief and factual to nuanced analyses with textual evidence. Additionally, responses to analytical questions were 30% longer than those to factual questions, showcasing improved language production with more complex sentence structures and diverse vocabulary. Teachers utilized interrogative modality as an effective formative assessment tool to identify misconceptions and adjust teaching strategies in real-time. The findings indicate a shift from traditional IRE (Initiation-Response-Evaluation) patterns toward more dialogic IRF (Initiation-Response-Feedback) interactions, highlighting the need for professional development focused on strategic use of interrogative modality in English language learning contexts in Indonesia.